Premature ovarian insufficiency in young girls: repercussions on uterine volume and bone mineral density. (9th September 2014) - Bakhsh, Hanadi; Dei, Metella; Bucciantini, Sandra; Balzi, Daniela; Bruni, Vincenzina
Abstract: Study objective : To evaluate biological differences among young subjects with premature ovarian insufficiency (POI) commencing at different stages of life. Design : Retrospective observational study. Setting : Careggi University Hospital Participants : One hundred sixty-two females aged between 15 and 29 years with premature ovarian insufficiency. Methods : Data were collected as a retrospective chart review of baseline evaluation at diagnosis of premature ovarian insufficiency (POI). About 162 participants were divided into four groups based on gynecological age. Two primary outcome variables (uterine development and bone mineral density (BMD)) were analyzed in terms of differences among groups and in a multivariate logistic regression analysis. Results : Uterine development was clearly jeopardized when estrogen insufficiency started at a very young age. Total body BMD showed significant differences among the four groups studied, clearly corresponding to the duration of ovarian function. Data were discussed in relation to the choice of hormone replacement therapy regimens. Chinese abstract: 评估年轻患者不同阶段发生卵巢功能不全（POI）的生物学差异。回顾性观察研究。设置：Careggi大学医院。对象：162名15岁～29岁卵巢功能不全女性。对诊断为卵巢功能不全（POI）的基线数据进行了回顾性分析。162名参与者根据妇科年龄分为四组。分析不同组的两个主要指标（子宫发育和骨密度（BMD）），并进行多因素logistic回归分析。雌激素不足开始于非常年轻的年龄时子宫发育明显受影响。不同四组的总BMD有显著差异，与卵巢功能的持续时间有明确的相关性。数据讨论了相关的激素治疗方案的选择。